2007
DOI: 10.3892/ijmm.19.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BRCC3, a novel cell cycle regulated molecule, is associated with increased phospho-ERK and cell proliferation

Abstract: Raf-1 protein serine/threonine kinase plays an important role in ERK signal transduction pathway of cell survival and proliferation. Raf-induced transcriptional changes are dependent on phosphorylation/activation of ERK. However, regulation of phospho-ERK (p-ERK) via Raf transcriptome is as yet unknown. We report the initial characterization of BRCC3, a novel gene discovered previously by mRNA expression profiling in MDA-MB 231 human breast cancer cells treated with Raf antisense oligonucleotide. BRCC3 is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…1). These genes were, SET translocation (SET) [15], DEAD (Asp-Glu-Ala-Asp) box polypeptide 1 (Ddx1) [16], COMM domain containing 3 (Commd3) [17] and BRCA1/BRCA2-containing complex, subunit 3 (Brcc3) [18]. SET has been assumed to play a role in nucleosome assembly [15].…”
Section: Resultsmentioning
confidence: 99%
“…1). These genes were, SET translocation (SET) [15], DEAD (Asp-Glu-Ala-Asp) box polypeptide 1 (Ddx1) [16], COMM domain containing 3 (Commd3) [17] and BRCA1/BRCA2-containing complex, subunit 3 (Brcc3) [18]. SET has been assumed to play a role in nucleosome assembly [15].…”
Section: Resultsmentioning
confidence: 99%
“…Within several of the conserved MIGs identified herein, mutations have been linked to abnormal cell proliferation or cancer in humans. For example, mutations in BRCC3, which encodes a cell cycle regulator involved in G2/M phase transition, has been linked to myelodysplastic syndrome (MDS), as well as breast and cervical cancers (Boudreau et al 2007;Huang et al 2015;Zhang, Zhou 2018). Mutations in E2F3 have been associated with retinoblastoma, bladder and lung cancer (Ziebold et al 2001;Wang et al 2017a;Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings indicate that regulation of TRIO and DEPDC1B expression by Pitx2 leads to the activation of RAC1 and RHOA, thus contributing to the regulation of cell migration during embryonic development. Although a role for DEPDC1B in the regulation of cell migration during embryonic development remains to be elucidated, studies using cultured cells have demonstrated that DEPDC1B is implicated in the regulation of cell migration and cell proliferation [57-59]. …”
Section: Discussionmentioning
confidence: 99%